2011
DOI: 10.1590/s0102-311x2011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Pandemia de Influenza A (H1N1): mudança nos hábitos de saúde da população, Cachoeira do Sul, Rio Grande do Sul, Brasil, 2010

Abstract: This quantitative exploratory-descriptive study conducted from January 5 to February 26, 2010, focused

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
2
0
3
Order By: Relevance
“…Study in southern Brazil also showed broad information on Influenza A (H1N1) among the population (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Study in southern Brazil also showed broad information on Influenza A (H1N1) among the population (26) .…”
Section: Discussionmentioning
confidence: 99%
“…C'est possible parce que ce sont des régions où l'hiver est plus fréquent, ce qui favorise la transmission du virus de la grippe (MARQUES et coll., 2011). Les soins d'hygiène sont réduits parce qu'il s'agit d'une période plus froide, où les espaces fermés demeurent et où les agglomérations de personnes ne sont pas évitées, comme aux périodes plus chaudes (MILANESI, CAREGNATO et WACHHOLZ, 2011). L'hiver dans ces régions attire de nombreux touristes de tout le Brésil et d'autres pays vers ces régions, ce qui conduit à une plus grande transmission du virus (GRECO et al, 2009).…”
Section: Discussionunclassified
“…Esta discusión adquiere escasa resonancia en Brasil 41,42,43,44,45,46,47 y en Argentina 37,48,49 , tanto a nivel de los medios masivos de comunicación, como de la producción científica.…”
Section: Discussionunclassified